2012
DOI: 10.1016/j.jmb.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

CheA–Receptor Interaction Sites in Bacterial Chemotaxis

Abstract: In bacterial chemotaxis, transmembrane chemoreceptors, the CheA histidine kinase, and the CheW coupling protein assemble into signaling complexes that allow bacteria to modulate their swimming behavior in response to environmental stimuli. Among the protein-protein interactions in the ternary complex, CheA-CheW and CheW-receptor interactions were studied previously, whereas CheA-receptor interaction has been less investigated. Here, we characterize the CheA-receptor interaction in Thermotoga maritima by NMR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 50 publications
(73 reference statements)
8
83
0
Order By: Relevance
“…1B). This P3-P4 linker has been shown to be central to kinase activity and control, specifically basal autophosphorylation, kinase activation, and initiation of longrange structural and dynamic changes impinging on the active site (21)(22)(23). Thus, the P3-P4 linker could be a conduit through which allosteric inhibition passes from an inhibited P4 catalytic domain to the P3 helical bundle, and from P3 to inhibit the P4' catalytic domain of the companion kinase protomer.…”
Section: Discussionmentioning
confidence: 99%
“…1B). This P3-P4 linker has been shown to be central to kinase activity and control, specifically basal autophosphorylation, kinase activation, and initiation of longrange structural and dynamic changes impinging on the active site (21)(22)(23). Thus, the P3-P4 linker could be a conduit through which allosteric inhibition passes from an inhibited P4 catalytic domain to the P3 helical bundle, and from P3 to inhibit the P4' catalytic domain of the companion kinase protomer.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that both CheV1 and CheW cause CheA to be more active, with CheW triggering greater activation. Previous work has shown that CheA activation is maximal with coupling proteins (24,25).…”
Section: Chew and Chev1 Both Form Direct Interactions With Chea Andmentioning
confidence: 95%
“…The tip contains determinants for binding CheA [911] and CheW [10, 12, 13] and for forming trimers of receptor dimers [14, 15]. The five E. coli members of the MCP family (Tar, Tsr, Tap, Trg, and Aer) have identical trimer contact residues, enabling low-abundance receptors (Tap, Trg, and Aer) to participate in signaling teams with high-abundance partners (Tar and Tsr) [15, 16].…”
Section: Structural Features Of Chemoreceptor Moleculesmentioning
confidence: 99%